Analysis of the Educational Impact of M-Learning and Related Scientific Research - Javier Fombona; María Angeles Pascual; Miguel Pérez Ferra (Springer, 2020)
Abstract The deep penetration and global impact of mobile devices has led the scientific community to undertake a thorough analysis of the implications of this phenomenon. Researchers need to determine their true real effect and how they can best be used to manage information and build knowledge. This study has examined recent investigations on the subject of mobile learning and carried out a descriptive analysis of a sample of registers indexed on the Web of Science research platform in 2015-16. An exhaustive content analysis has revealed new areas where M-Learning is being implemented, especially in the teaching of foreign languages, the emergence of social interaction methodologies in Secondary Education, evolving forms of collaborative relationships, work with clearly defined student profiles and the use of virtual immersive and innovative spaces in Higher Education. This paper also emphasizes the presence of previously unknown, transcendent problems associated with M-learning, such as the collateral addiction effect, and its interference in the classroom. Finally, our study suggests that teachers could embrace these technological proposals and include them in their strategies. Indeed, it might be necessary to flip the process, so this research could be the start of the generation and design of innovative guidelines to manage these forms and content.